Dietary nutrient intake related to higher grade cervical intraepithelial neoplasia risk: a Chinese population-based study - Zhe Wang; Aimin Yang; Jing Yang; Weihong Zhao; Zhilian Wang; Wei Wang; Jintao Wang; Jinghui Song; Li Li; Weiguo Lv; Dongyan Li; Huiqiang Liu; et al. (Nutrition & Metabolism, 2020)
Abstract Background Dietary nutrient intake plays a significant role in carcinogenesis. Few studies have investigated the association between dietary nutrient intake and cervical intraepithelial neoplasia (CIN) risk in China. Methods Data on 2304 women from an ongoing cohort comprising 40,000 women from China in 2014 were included. Study randomly selected 218 out of 2304 people as subjects during 2019. All participants were surveyed through in-person interviews, physical examinations, and laboratory tests. Clinical data were obtained from physical examinations and laboratory tests. Dietary intakes were assessed using a semiquantitative food frequency questionnaire. Nutrition intakes from 26 food sources were calculated using a comprehensive validated database. Descriptive statistics were used to describe the frequency and proportion, and mean and standard deviation of the demographic characteristics. Characteristics were examined for significant differences, and Pearson chi-square tests were used for categoric variables. Logistic regression was used to obtain odds ratios (ORs) and confidence intervals (CIs) for CIN risk in each nutrient intake quartile relative to that in the highest quartile. Results The food frequency questionnaire exhibited acceptable reproducibility and reasonable validity in assessing nutrient intakes among these women. After adjusting for multiple confounders, several dietary nutrients showed significant associations with CIN2+ risk. Low dietary folate intake was associated with the risk of CIN2+ (first versus fourth quartile: OR = 1.55, 95% CI 1.03–2.33). Similar results were also observed for vitamin B6 (OR = 1.63, 95% CI 1.08–2.46), vitamin C (OR = 1.59, 95% CI 1.05–2.42), niacin (OR = 1.65, 95% CI 1.08–2.51), and vitamin K (second versus fourth quartile: OR = 1.60, 95% CI 1.05–2.44). Conclusions Low folate; vitamin B6, C, and K; and niacin intakes were associated with CIN2+ risk. Nutrients may influence the development of higher grade CIN and cervical cancer. Trial registration The study was registered in the Chinese Clinical Trial Register (ChiCTR-ROC-15006479) ( https://www.chictr.org.cn ).